Standing, Active vs Sitting, Torpid: a Management Decision - Usman, Bustami; Champion, Ibrahim; Muslem, Asnawi; Samad, Iskandar Abdul (AT-TALIM, 2018)
The aim of the study is to investigate the pros and cons of standing while working and studying. A qualitative research was employed where the data taken from education practitioners and students interested to learn and support the introduction of standing desks. The finding of the study show that students and sedentary workers now spend up to 85% of their waking hours,(+/-13.5 hrs/day), sitting viz: sitting at meals, sitting in transportation, sitting in schools or offices, sitting watching TV or looking at a handphone or an i-pad plus sitting whilst watching sport or playing computer games. Even if standing in classes became the default behaviour in all classes it could only result in a maximum of about 20 extra hours of standing per week during semesters and thus could only reduce the amount of time spent sitting by a maximum of 14% of waking hours to 71% of waking hours. The height of Standing Desks should be at the elbow height of theÂ  person concerned ie about 1.00m for senior high school and university students and adults. For primary school students the desk height for the standing desk is about 75cm â ie. the same as the desk height for normal sitting desks for adults. The study also did a small survey of educators, 66% of whom would support the introduction ofÂ  standing desks.Â  Finally the study found that 72 % of the students and their teacher supported the introduction of standing desks. It is hoped that some schools and offices will take the initiative to introduce standing desks on a larger scale.